Quantification of Mycobacterium tuberculosis and Mycobacterium avium complex in human immunodeficiency virus-infected individuals with and without tuberculosis - Naishadham, Yashovardhan; Jogishetty, Vijay; Pacha, Venkat; Balla, Sudheer; Vinay, B; Naishadham, Parameshwar (Journal of oral and maxillofacial pathology : JOMFP, 2019)
Context: For a dental practitioner, HIV-TB co-infection which is a lethal aliment is an occupational hazard by the virtue of abundant aerosol formation in day to day dental practice. Aim: To assess the prevalence of TB co-infection among HIV patients. To assess the infectivity by culturing Mycobacterium Tuberculosis and Mycobacterium avium complex using Lowenstein Jensen medium and Middlebrook medium. Setting and Design: One hundred and forty one recently diagnosed HIV seropositive patients were selected. They were divided into two group based on their clinical symptomatology. Sputum samples, CD4 counts and brief case history were collected from these patients. Subjects and Methods: Sputum samples were homogenized using modified Petroff's method. The samples were cultured using Lowenstein Jensen and Middlebrook media. Cultures were interpreted after two weeks of incubation and the cultures were quantified based on their number of colonies produced on them. Statistical Analysis: Descriptive statistical analyses followed by Chi square test were performed to assess the prevalence and variation of TB co-infection. Results: Prevalence of TB in our sample is 25.53%. Higher CFU of MTB and MAC are obtained in patients symptomatic for TB. MB yields higher CFU than LJ. Conclusion: Clinical symptoms alone cannot act as basis for suspecting TB in HIV patients. Mycobacterial cultures should be used as diagnostic aids and preferably both the mediums have to be used.